2020
DOI: 10.1111/jog.14236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of uterine artery occlusion during myomectomy on ovarian reserve: Serial follow‐up of sex hormone levels, ultrasound parameters and Doppler characteristics

Abstract: Aim: To evaluate the influence of uterine artery occlusion at myomectomy (UAO + M) on ovarian reserve based on serum sex hormone levels, ultrasound and color Doppler examinations. Methods: In this cohort study, nine women with symptomatic uterine myomas underwent UAO + M were recruited. Each woman was assessed preoperatively and 3, 6 months postoperatively, through a serial of hormonal, ultrasound parameters and Doppler examination for ovarian stromal blood flow. The data were analyzed using generalized estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Although the AMH level decreased between pre-surgery and second-day values, this was not statistically significant. Similar findings have been reported by Chen et al [18], Mehdizadehkash et al [14], Sander et al [16], and Farag et al [21]. It did, however, differ from the of Aharon et al [15], Brown et al [19], Migahed et al [20], and Wang et al [22],…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although the AMH level decreased between pre-surgery and second-day values, this was not statistically significant. Similar findings have been reported by Chen et al [18], Mehdizadehkash et al [14], Sander et al [16], and Farag et al [21]. It did, however, differ from the of Aharon et al [15], Brown et al [19], Migahed et al [20], and Wang et al [22],…”
Section: Discussionsupporting
confidence: 83%
“…Several studies using AMH found no significant effect on ovarian function after myomectomy when the uterine tourniquet was used; however, other studies revealed a transient or short-term change in ovarian function after myomectomy [16] [17] [18]. Concerns have been raised that the ischaemic reperfusion injury caused by the single tourniquet approach, which is commonly used to limit blood loss during abdominal myomectomy, may diminish or modify ovarian reserve, affecting conception.…”
Section: Introductionmentioning
confidence: 99%
“…Angelica can nourish blood and promote blood circulation. Herba Taxilli can reinforce the liver and kidney and strengthen the bones and muscles (Abdelnaby et al, 2020;Chen et al, 2020). Clinical research experiments have shown (Liu et al, 2019) that excessive androgen in the ovaries will also inhibit follicular maturation, thereby blocking further follicular development, and hindering normal formation of highquality follicles.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] However, studies have reported no reduction in AMH levels following uterine artery occlusion or embolization. [22][23][24] These conflicting reports highlight the uncertainty surrounding the relationship between blood flow the uterus and ovarian reserve, marking it as an area for future investigation.…”
Section: Discussionmentioning
confidence: 99%